Anti-icing conductive coating for overhead contact system and preparation method thereof
Patent Information
- Application Number
- CN202611152640.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-08-28
AI Technical Summary
[0005]鉴于此,本申请实施例的目的在于提供一种接触网用防覆冰导电涂料及其制备方法,以解决现有技术中防覆冰涂料产品不适用于接触网的问题
1.本申请提供的涂料,电导率达到6×107μS/m以上,电阻率达到0.018Ω·mm2/m以下,导电性接近紫铜的65%,可以有效满足受电弓从接触网的取电需求。
Smart Images

Figure CN122648016A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating preparation technology, specifically relating to an anti-icing conductive coating for contact wires and its preparation method. Background Technology
[0002] The overhead contact line is the only special transmission line in the electric traction power supply system that supplies power to locomotives. It is erected above the track via supports and cantilever arms. The contact line is constantly exposed to various natural environments and is highly susceptible to external factors such as climate and terrain. In recent years, due to changes in the natural environment, icing of the contact line has become frequent. After icing, the pantograph's current-collecting performance decreases, reducing the safety and reliability of the contact line. It also causes severe mechanical wear and arcing erosion on the contact wire, and the resulting arcs can prevent trains from drawing power normally, affecting their normal operation. Furthermore, icing-induced galloping of the contact line and ice flashover of the insulators can cause short circuits in the contact line, even leading to pantograph-contact line accidents, resulting in partial or large-scale damage and shutdown of the contact line, further escalating the disaster and seriously affecting line safety.
[0003] Current contact network anti-icing and de-icing technologies are relatively outdated, mainly relying on heaters and ice scrapers to heat or remove accumulated ice from the contact network. However, some problems exist in practical applications. For example, the de-icing effect of the devices may be affected in severe weather; the maintenance and upkeep of de-icing equipment also require a significant investment of manpower and resources; and de-icing devices need to be operated at heights, thus posing certain safety risks.
[0004] In recent years, the coatings industry has gradually researched and developed some anti-icing coatings for power transmission lines to address the low-temperature icing problem of long high-voltage transmission lines. However, these coatings suffer from performance issues such as poor anti-icing effect, low wear resistance, non-conductivity, and low natural de-icing rate, making them unsuitable and unable to effectively solve the icing problem of overhead contact lines. Summary of the Invention
[0005] Therefore, the purpose of this application is to provide an anti-icing conductive coating for contact wires and its preparation method, to solve the problem that existing anti-icing coatings are not suitable for contact wires. The coating provided in this application provides photothermal anti-icing effects while ensuring conductivity, and exhibits excellent hydrophobic and oleophobic properties, effectively reducing the accumulation of rainwater or snow on the contact wire. It has good wear resistance, strong adhesion, good toughness, and resistance to microcracks, showing broad application prospects. Furthermore, the coating provided in this application also has the ability to emit light under UV light, which, combined with machine recognition technology, can quickly detect icing points and coating damage points, facilitating subsequent inspection and maintenance.
[0006] The embodiments of this application are implemented as follows: A conductive coating for contact wires that prevents icing includes component A and component B. By weight, component A comprises 12-25 parts modified fluorosilicone resin, 0.6-1.2 parts fluorinated modified nano-SiO2, 2-4 parts TiN / graphene composite material, 2-4 parts graphene / carbon fiber composite material, 2-4 parts tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer, 1-2 parts metal powder, 1-3 parts superconducting carbon black, 0.1-0.5 parts adhesion promoter, 0.2-0.6 parts wetting and dispersing agent, 0.1-0.3 parts defoamer, and 60-80 parts solvent; component B comprises 1.5-4 parts polyisocyanate curing agent. The tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer comprises molecules with the structure shown in formula (1): , structure (1); where n = 15 ~ 50.
[0007] Furthermore, the preparation method of the TiN / graphene composite material includes the following steps: S1. By mass, add 30 parts of TiN powder to 70 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain TiN dispersion; S2. Add 10 parts of graphene to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain a graphene dispersion; S3. Mix the TiN dispersion and graphene dispersion at a mass ratio of 1:1, heat and disperse for 1 hour, and then dry.
[0008] Furthermore, the preparation method of the graphene / carbon fiber composite material includes the following steps: S1. By mass, add 10 parts of graphene powder to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain a graphene dispersion. S2. Add 10 parts of carbon fiber to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and ultrasonically disperse to obtain a carbon fiber dispersion; S3. Mix the graphene dispersion and carbon fiber dispersion at a mass ratio of 1:1, disperse by ball milling, and then dry.
[0009] Furthermore, the preparation method of the tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer includes the following steps: S1. Place 4-carboxytetraphenylethylene, hydroxyl-terminated silicone oil and anhydrous dichloromethane in a reactor and stir until dissolved under a nitrogen atmosphere; S2. After adding 4-dimethylaminopyridine, cool to 0-5°C and add N,N'-dicyclohexylcarbodiimide while stirring; after the addition is complete, return to room temperature. S3. Stir the reaction continuously at room temperature for 24–36 hours; S4. The reactants are filtered, concentrated, purified, washed, dried and purified.
[0010] Furthermore, the 4-carboxytetraphenylethylene in step S1 of the method for preparing tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer includes the following steps: S11. Under a nitrogen atmosphere, 4-formyltetraphenylethylene is placed in a reactor, anhydrous acetone is added and stirred until dissolved; S12. Cool to 0-5℃, and slowly add Jones' reagent dropwise while stirring; after the addition is complete, raise to room temperature and stir the reaction for 1-2 hours. S13. Add isopropanol solution and stir, then extract using an extractant, which can be either dichloromethane or ethyl acetate; S14. Wash with deionized water and saturated sodium chloride solution, then dry with anhydrous sodium sulfate, filter and collect the filtrate, and concentrate by rotary evaporation to obtain the finished product.
[0011] Furthermore, step S4 in the method for preparing tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer specifically includes: Filter the reactants to remove solid impurities and collect the filtrate. Then concentrate the filtrate to one-third of its volume, add 3 to 5 times its volume of diethyl ether and place it in an environment below 0°C for cold precipitation to remove impurities. Filter to remove solid impurities and obtain an organic phase filtrate. Wash the filtrate successively with dilute hydrochloric acid solution, saturated sodium bicarbonate solution and saturated sodium chloride solution, then dry it with anhydrous sodium sulfate, filter to collect the filtrate and concentrate it by rotary evaporation to remove the solvent.
[0012] Furthermore, the metal powder is in flake form and its components include at least one of silver powder and copper powder.
[0013] Furthermore, the specific surface area of the superconducting carbon black powder is 400–500 m². 2 / g.
[0014] Furthermore, the wetting and dispersing agent is polyvinylpyrrolidone.
[0015] This application also provides a method for preparing an anti-icing conductive coating for overhead contact lines, comprising the following steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to a dispersion tank, add some solvent, and stir and disperse at 600-900 rpm for 3-5 min; S2. Reduce the rotation speed to 300-400 rpm, slowly add the tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer, and after the addition is complete, increase the rotation speed to 1000-1200 rpm and stir to disperse for 15-30 minutes. S3. Reduce the rotation speed to 300-400 rpm, slowly add metal powder and superconducting carbon black, and after adding, increase the rotation speed to 1000-1500 rpm, stir and disperse for 10-15 minutes, and then transfer to a sand mill for grinding until the fineness is less than 80 μm. S4. Transfer the material back to the dispersion tank and stir and disperse at 300-500 rpm for 3-5 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1000-1500 rpm and stir and disperse for 20-25 minutes. S5. Reduce the rotation speed to 300-500 rpm, add adhesion promoter, defoamer and remaining solvent, and stir at 1000-1500 rpm for more than 10 minutes to obtain ingredient A for later use; S6. Add the polyisocyanate curing agent to the dispersion tank and disperse it at 600-900 rpm for 5-8 min to obtain ingredient B for later use; S7. By weight, mix 100 parts of ingredient A with 1.5 to 4 parts of ingredient B and stir until homogeneous.
[0016] Compared with the prior art, the beneficial effects of this application are: 1. The coating provided in this application has an electrical conductivity of 6×10⁻⁶. 7 With a resistivity of over μS / m, the resistivity reaches 0.018 Ω·mm. 2 With a current of less than / m, its conductivity is close to 65% of that of pure copper, which can effectively meet the power demand of the pantograph from the contact network.
[0017] 2. The coating provided in this application possesses excellent superhydrophobicity and oleophobicity, thereby reducing the amount of ice accumulating on the contact wire under low-temperature conditions and lowering the icing force (horizontal icing force below 15N). It also exhibits good photothermal properties, allowing the coating to heat up by more than 25°C in 60 seconds under one solar intensity, thus achieving natural de-icing under low-temperature conditions and improving the de-icing rate (de-icing rate exceeding 95%). This invention can be applied to the coating of contact wires for various railways, achieving the goal of reducing coating icing and ensuring the normal operation of trains under low-temperature and severe weather conditions. It has high economic value and broad application prospects.
[0018] 3. The coating provided in this application has good wear resistance, strong adhesion to the substrate, good flexibility, and stable properties after drying. It is also tensile-resistant and not easily cracked or damaged by wear.
[0019] 4. The coating provided in this application has the ability to emit light under UV light, and the light emission is uniform and the light stability is excellent. In the later maintenance process, it can be used in conjunction with drones that can emit UV light and identify fluorescence, automated detection equipment, etc., to quickly detect freezing points or coating damage points, so as to facilitate further treatment or coating maintenance. Attached Figure Description
[0020] Figure 1 The chemical reaction formula for the synthesis of the tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer provided in the embodiments of this application is shown. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. The illustrative embodiments and descriptions of this application are for explanation only and are not intended to limit the scope of this application. Any product identical or similar to this application, derived by any person based on the teachings of this application or by combining features of this application with other prior art, falls within the protection scope of this application.
[0022] Specific experimental steps or conditions not specified in the embodiments can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of this application and are not necessarily drawn to scale. The same reference numerals in the drawings indicate the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0023] Explanation of proper nouns: BYK-4511: A commercially available finished tackifier that promotes adhesion, manufactured by BYK GmbH, Germany; a polymer tackifier for solvent-free and solvent-based (also high solids) two-component epoxy resin systems and baking systems.
[0024] BYK-A530: A commercially available defoaming / defoaming agent manufactured by BYK GmbH, Germany; used in solvent-based and solvent-free coatings, especially suitable for epoxy resin systems, it can reduce defects such as fisheyes, craters and dark bubbles in the coating film.
[0025] N3390: A commercially available aliphatic polyisocyanate curing agent manufactured by Covestro; primarily used as a curing component in two-component polyurethane coatings, characterized by good weather resistance, non-yellowing, and strong gloss retention. This application provides an anti-icing conductive coating for overhead contact lines, comprising component A and component B. Component A, by mass parts, comprises: 12-25 parts of modified fluorosilicone resin; further, the modified fluorosilicone resin is preferably a fluorosilicone resin with a solid content of not less than 50% and a fluorine content of not less than 26%. The modified fluorosilicone resin molecular chain has multiple hydroxyl groups, which can react with the isocyanate groups in the curing agent to form urethane bonds, forming a cross-linked network and completing the curing process of the coating. The modified fluorosilicone resin selected in this application is a commercially available finished product, manufactured by Shandong Huafu Chemical Co., Ltd.
[0026] 0.6–1.2 parts of fluorinated modified nano-SiO 2, The fluorinated modified nano-SiO2 was prepared by the following method: Clean nano-SiO2 powder was placed in deionized water and stirred at high speed for 30 minutes to disperse it evenly, forming a 20% (w / w) dispersion. The mixture was heated to 50°C and stirred continuously. Fluorinated silazane was slowly added dropwise, and after the addition was complete, the temperature was raised to 80°C, and the mixture was catalytically refluxed for 4 hours. After the reaction was complete, the reactants were removed, dried at 70°C for at least 6 hours, and then ground to obtain fluorinated modified nano-SiO2 powder.
[0027] Furthermore, the molar ratio of nano-SiO2 to fluorinated silazane is 1:(1 to 1.02), and the fluorinated silazane is either perfluorooctyldiethoxysilazane or tridecafluorooctyldiethoxysilazane, with the nano-SiO2 preferably having a particle size of 50 to 100 nm.
[0028] This fluorinated modified nano-SiO2 is used as a reinforcing filler in coatings. Through modification, the carboxyl and alkoxy groups at one end of the nano-silica react to form strong chemical bonds, tightly connecting with the fluorinated long chains. While retaining excellent wear resistance, the extension of the fluorinated long chains significantly reduces the surface energy of the silica, transforming it from a hydrophilic to a superhydrophobic state, effectively improving the hydrophobic and oleophobic properties of the coating. Furthermore, the modified nano-silica treated with fluorinated silazane exhibits better compatibility with fluorosilicone resins, resulting in a denser overall structure of the coating and superior wear resistance.
[0029] 2-4 parts of TiN / graphene composite material, the preparation method of which includes the following steps: S1. By mass, take 30 parts of TiN powder and add it to 70 parts of solvent, add 1 part of polyvinylpyrrolidone dispersant, and ultrasonically disperse for 30 minutes to make it uniformly dispersed to obtain TiN dispersion; S2. Add 10 parts of graphene to 90 parts of solvent, add 1 part of polyvinylpyrrolidone dispersant, and ultrasonically disperse for 30 minutes to make it uniformly dispersed, thus obtaining a graphene dispersion. S3. Mix TiN dispersion and graphene dispersion at a mass ratio of 1:1, heat to 50°C and ultrasonically disperse for 1 hour, then dry the mixed dispersion to obtain TiN / graphene composite material.
[0030] The solvent used in the above method is a mixture of butyl acetate and PMA, with a mass ratio of butyl acetate to PMA of (1-2):1. The TiN / graphene composite material prepared by this method exhibits physical adsorption effects and strong interfacial interactions. TiN nanoparticles are adsorbed onto the graphene surface or between graphene sheets, forming a physically connected rather than chemically bonded TiN / graphene composite material. In this composite material, TiN nanoparticles expand the graphene sheets, preventing their π-π stacking and reducing the percolation threshold; graphene encapsulates and isolates TiN, preventing severe agglomeration. When used in a coating matrix, this composite material constructs a more continuous and uniform conductive and thermally conductive network. Furthermore, graphene fills the pores between TiN particles, increasing density and significantly reducing the corrosion rate, thus providing better anti-corrosion performance for the coating. Additionally, TiN provides rigid support between graphene layers, reducing interlayer slippage and resulting in better wear resistance. In summary, both TiN and graphene have good electrical conductivity. Compared with using TiN and graphene materials independently, TiN / graphene composite coatings have better electrical conductivity, thermal conductivity, wear resistance, and corrosion resistance.
[0031] 2–4 parts of graphene / carbon fiber composite material, which is prepared by the following method: S1. By mass, add 10 parts of graphene powder to 90 parts of solvent, add 1 part of polyvinylpyrrolidone dispersant, and ultrasonically disperse for 30 minutes to obtain a graphene dispersion. S2. Add 10 parts of carbon fiber to 90 parts of solvent, add 1 part of polyvinylpyrrolidone dispersant, and ultrasonically disperse for 30 minutes to obtain carbon fiber dispersion; S3. Mix the graphene dispersion and carbon fiber dispersion at a mass ratio of 1:1, then ball mill and disperse for 24 hours. Dry the resulting mixed dispersion to obtain the graphene / carbon fiber composite material.
[0032] The solvent used in the above method is a mixture of butyl acetate and PMA, with a mass ratio of butyl acetate to PMA of (1-2):1. The graphene / carbon fiber composite material prepared by this method, compared to its independent use in coatings, can both inhibit severe fiber agglomeration and prevent complete stacking of graphene sheets; it lowers the percolation threshold and exhibits stronger electrical and thermal conductivity. It also improves the interfacial shear strength of the fiber / matrix and provides better toughness. The graphene sheets coating or overlapping the carbon fiber surface and interfiber gaps achieve an organic combination of the planar structure of graphene and the linear structure of carbon fiber, forming a three-dimensional network structure. Together, they construct a lower threshold and a more uniform electrical and thermal conductivity network. When used in combination in coating systems, this results in superior photothermal effects.
[0033] 2 to 4 parts of tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer (hereinafter referred to as: TPE-PDMS-OH polymer), the polymer comprising molecules with the structure shown in structural formula (1): The structure is (1); where n is an integer from 15 to 50.
[0034] The TPE-PDMS-OH polymer has -OH groups on its side chains, which can react with the -NCO groups in the curing agent, achieving the effect of covalently embedding the TPE-PDMS-OH polymer into the polyurethane crosslinking network. After curing, the movement of PDMS chain segments is restricted, and TPE units aggregate. Based on the intramolecular rotational restriction mechanism, the cured coating can emit blue-green fluorescence under UV light. Furthermore, the TPE units are covalently locked to the PDMS chains, and as the PDMS chain segments are embedded in the fluorosilicone resin crosslinking network, they do not migrate or precipitate, resulting in uniform luminescence and superior photostability. Based on this design, it can be used in conjunction with drones that emit UV light and detect fluorescence during later maintenance to quickly identify freezing points or coating damage points, facilitating further treatment or coating maintenance.
[0035] In addition, TPE-PDMS-OH polymer has flexible long chains and contains rigid aromatic ring structures in its molecules, which can restrict the slippage of long chain molecules. When used as a dopant in fluorosilicone resin, it can enhance the flexibility of the coating, absorb strain energy, inhibit brittle cracking of the coating, improve the tensile strength of the coating, and enhance the coating's resistance to microcracks and adhesion to the metal substrate.
[0036] This TPE-PDMS-OH polymer is prepared by esterification coupling reaction of carboxylated tetraphenylethylene and hydroxyl-terminated silicone oil. Its chemical reaction formula is shown in the attached... Figure 1 Furthermore, the preparation method includes the following steps: S1. Using a molar mass meter, take 1 part of 4-carboxytetraphenylethylene, 3-5 parts of terminal hydroxyl silicone oil and an appropriate amount of anhydrous dichloromethane and place them in a reactor. Under nitrogen atmosphere protection, stir at room temperature until dissolved. S2. Maintain a nitrogen atmosphere, add 0.1 to 0.2 parts of 4-dimethylaminopyridine catalyst, and stir for 10 minutes; then place the reactor in an ice-water bath (0 to 5°C), add 1 to 1.5 parts of N,N'-dicyclohexylcarbodiimide and keep stirring; after the addition is complete, remove the ice-water bath and slowly warm it to room temperature; S3. Maintain a nitrogen atmosphere and stir continuously at room temperature for 24–36 hours to carry out the esterification coupling reaction; S4. Filter the reactants to remove solid impurities and collect the filtrate; then concentrate the filtrate to one-third of its volume, add 3 to 5 times its volume of diethyl ether and place it in an environment below 0°C for cold precipitation to remove impurities for 2 to 4 hours; filter to remove solid impurities and obtain an organic phase filtrate. S5. Wash the filtrate sequentially with dilute hydrochloric acid solution, saturated sodium bicarbonate solution and saturated sodium chloride solution, then dry with anhydrous sodium sulfate for 30 minutes, filter and collect the filtrate, and concentrate by rotary evaporation to remove the solvent to obtain a viscous liquid TPE-PDMS-OH polymer.
[0037] Furthermore, the preparation method of 4-carboxytetraphenylethylene in step S1 includes the following steps: S11. Using a molar volumetric calibrator, take 1 part of 4-formyltetraphenylethylene and place it in the reactor. Under a nitrogen atmosphere, add an appropriate amount of anhydrous acetone and stir until dissolved to obtain a clear liquid. S12. Place the reactor in an ice-water bath (temperature 0-5℃), and slowly add 3 parts of chromic acid solution dropwise while stirring; the preferred chromic acid solution is Jones' reagent, which is a dilute sulfuric acid solution of chromium trioxide; S13. After the addition is complete, remove the ice water bath and keep stirring. Slowly raise the temperature to room temperature and continue stirring for 1 to 2 hours. S14. Add an appropriate amount of isopropanol solution and stir for 10 minutes to quench the chromic acid trioxide solution; then add the extractant and an appropriate amount of deionized water, and wash 2-3 times with deionized water and saturated sodium chloride solution after extraction; the extractant is preferably any one of dichloromethane or ethyl acetate. S15. Dry with anhydrous sodium sulfate for 30 minutes, filter and collect the filtrate, and concentrate by rotary evaporation to obtain 4-carboxytetraphenylethylene, which is a pale yellow solid.
[0038] One to two parts of metal powder, preferably with a particle size of 15 to 30 nanometers and a flake-like shape; the metal powder is preferably silver powder and / or copper powder. The flake-like structure allows the silver powder and / or copper powder to form an overlapping continuous layer structure, thereby forming a continuous conductive channel.
[0039] 1 to 3 parts of superconducting carbon black, preferably with a specific surface area of 400 to 500 m². 2 / g powder, this specification is suitable for this coating system, achieves excellent conductivity and moderate oil absorption, reducing the occurrence of coating brittleness, cracking and other phenomena.
[0040] Furthermore, the combined use of superconducting carbon black and the TPE-PDMS-OH polymer in the formulation achieves a synergistic effect. This is because superconducting carbon black is predominantly porous with an extremely high specific surface area and a large oil absorption capacity. Using too little in the coating formulation makes it difficult to achieve the superconducting effect; using too much will cause the coating to become brittle due to excessive oil absorption, making it prone to breakage and significantly reducing adhesion. Adding the TPE-PDMS-OH polymer to the resin system before adding the superconducting carbon black allows the polymer's active groups to occupy the active sites on the carbon black surface, reducing the "connection" between the resin macromolecules and the carbon black. Moreover, the steric hindrance effect of the long chains of the TPE-PDMS-OH polymer prevents the carbon black aggregates from re-flocculating into a dense packing. In the dispersed state, the interparticle spacing is widened, and the apparent packing porosity decreases, resulting in a decrease in the oil absorption capacity of the superconducting carbon black. In summary, based on the applicant's proprietary formulation, the amount of superconducting carbon black can be appropriately increased compared to when the TPE-PDMS-OH polymer is not used, further improving the conductivity of the coating while ensuring its toughness.
[0041] 0.1 to 0.5 parts of adhesion promoter, preferably BYK-4511.
[0042] 0.2 to 0.6 parts of a wetting and dispersing agent, preferably polyvinylpyrrolidone.
[0043] 0.1 to 0.3 parts of defoamer, wherein the defoamer is a silicone polyether emulsion defoamer; more preferably, BYK-A530.
[0044] 60 to 80 parts of solvent, which includes a mixture of butyl acetate and propylene glycol methyl ether acetate (also known as PMA), with a mass ratio of butyl acetate to PMA of (1 to 2): 1.
[0045] Component B includes a polyisocyanate curing agent, which is used in an amount of 1.5 to 4 parts by weight. Further, the polyisocyanate curing agent is preferably N3390 curing agent.
[0046] The preferred mass ratio of component A to component B is 100:(1.5 to 4). That is, component A is prepared by dispensing to obtain component A, and component B is prepared to form component B. By mass, 100 parts of component A and 1.5 to 4 parts of component B are mixed and stirred evenly to obtain the anti-icing conductive coating for contact wires provided in this application.
[0047] This application also provides a method for preparing an anti-icing conductive coating for overhead contact lines, the specific steps of which include: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to a dispersion tank, add a portion of the solvent, and stir and disperse at 600-900 rpm for 3-5 minutes to fully wet the modified fluorosilicone resin. The mass of this portion of solvent should be 60%-80% of the total solvent mass.
[0048] S2. Reduce the rotation speed to 300-400 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1000-1200 rpm and disperse for 15-30 minutes.
[0049] S3. Reduce the rotation speed to 300-400 rpm, slowly add the metal powder and superconducting carbon black. After the addition is complete, increase the rotation speed to 1000-1500 rpm, disperse for 10-15 minutes, and then transfer to a sand mill for grinding until the fineness is less than 80 μm, ensuring that the metal powder and superconducting carbon black are fully and evenly dispersed.
[0050] S4. Transfer the material back to the dispersion tank and disperse it at 300-500 rpm for 3-5 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the rotation speed to 1000-1500 rpm and continue to disperse for 20-25 minutes.
[0051] S5. Reduce the rotation speed to 300-500 rpm, add the adhesion promoter, defoamer and remaining solvent, adjust to a suitable viscosity, stir at 1000-1500 rpm for more than 10 minutes, disperse evenly, filter and dispense to obtain ingredient A, for later use.
[0052] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse it at 600-900 rpm for 5-8 minutes, filter and dispense to obtain ingredient B, which is ready for use.
[0053] S7. By weight, mix 100 parts of ingredient A with 1.5 to 4 parts of ingredient B, and stir until homogeneous to obtain the anti-icing conductive coating for contact wires. It should be noted that ingredient A and ingredient B will solidify within a certain time after mixing, therefore, they should be applied and used as soon as possible after mixing. Therefore, the preparation method of the anti-icing conductive coating for contact wires provided in this application is applicable to specific construction site conditions, or ingredient A and ingredient B can be prepared in advance and mixed homogeneously at the construction site for use. At non-construction site conditions, please avoid mixing ingredient A and ingredient B to prevent premature curing of the coating and subsequent material waste.
[0054] The anti-icing conductive coating for overhead contact lines provided in this application is applicable to various construction methods such as brushing and spraying. Using this coating, a superhydrophobic, oleophobic, and conductive coating is formed. It possesses photothermal properties, absorbing light energy under natural light and converting it into heat energy through a non-radiative relaxation process, thus increasing its own temperature and enabling it to melt and remove ice, achieving an anti-icing effect. Furthermore, this coating exhibits strong adhesion to metal substrates, possesses toughness and corrosion resistance, and demonstrates excellent performance in practical applications. The coating also exhibits luminescence under UV light; when used in conjunction with automated UV luminescence and detection technologies such as drones, it can quickly detect icing points (if present) or coating damage points, greatly facilitating subsequent use and maintenance.
[0055] The following will further describe and illustrate the anti-icing conductive coating for contact wires provided in this application through examples and test cases.
[0056] Example 1: Prepare the raw materials according to the formula and dosage shown in Table 1 below.
[0057] Table 1: Raw Material Formula Table
[0058] In Table 1, BYK-4511, BYK-A530, and N3390 are all standard models of commercially available products, which can be purchased directly in the market by referring to the model numbers.
[0059] Mix component A to form ingredient A, mix component B to form ingredient B, and then prepare the coating by following these steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 60% of the solvent by mass, and stir and disperse at 600 rpm for 3 min.
[0060] S2. Reduce the rotation speed to 300 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1000 rpm and disperse for 30 min.
[0061] S3. Reduce the rotation speed to 300 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1000 rpm. After dispersing for 10 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0062] S4. Transfer the material back to the dispersion tank and disperse it at 300 rpm for 5 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1000 rpm and continue to disperse for 25 minutes.
[0063] S5. Reduce the rotation speed to 300 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1000 rpm for 12 minutes, filter and dispense to obtain ingredient A.
[0064] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse at 600 rpm for 5 min, filter and dispense to obtain ingredient B.
[0065] S7. By weight, mix 100 parts of ingredient A with 1.5 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0066] Example 2: Prepare the raw materials according to the formula and dosage shown in Table 2 below.
[0067] Table 2: Raw Material Formula Table
[0068] Mix component A to form ingredient A, mix component B to form ingredient B, and then prepare the coating by following these steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 80% of the solvent by mass, and stir and disperse at 900 rpm for 5 min.
[0069] S2. Reduce the rotation speed to 400 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1200 rpm and disperse for 15 min.
[0070] S3. Reduce the rotation speed to 400 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1200 rpm. After dispersing for 15 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0071] S4. Transfer the material back to the dispersion tank and disperse it at 400 rpm for 3 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1500 rpm and continue to disperse for 20 minutes.
[0072] S5. Reduce the rotation speed to 500 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1500 rpm for 10 minutes, filter and dispense to obtain ingredient A.
[0073] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse at 900 rpm for 8 min, filter and dispense to obtain ingredient B.
[0074] S7. By weight, mix 100 parts of ingredient A with 4 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0075] Example 3: Prepare the raw materials according to the formula and dosage shown in Table 3 below.
[0076] Table 3: Raw Material Formula Table
[0077] Mix component A to form ingredient A, mix component B to form ingredient B, and then prepare the coating by following these steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 70% of the solvent by mass, and stir and disperse at 800 rpm for 4 min.
[0078] S2. Reduce the rotation speed to 350 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1200 rpm and disperse for 25 min.
[0079] S3. Reduce the rotation speed to 350 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1300 rpm. After dispersing for 12 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0080] S4. Transfer the material back to the dispersion tank and disperse it at 400 rpm for 3 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1200 rpm and continue to disperse for 23 minutes.
[0081] S5. Reduce the rotation speed to 400 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1200 rpm for 15 minutes, filter and dispense to obtain ingredient A.
[0082] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse at 800 rpm for 5 min, filter and dispense to obtain ingredient B.
[0083] S7. By weight, mix 100 parts of ingredient A with 3 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0084] Example 4: Prepare the raw materials according to the formula and dosage shown in Table 4 below.
[0085] Table 4: Raw Material Formula Table
[0086] Mix component A to form ingredient A, mix component B to form ingredient B, and then prepare the coating by following these steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 80% of the solvent by mass, and stir and disperse at 900 rpm for 3 min.
[0087] S2. Reduce the rotation speed to 300 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1200 rpm and disperse for 20 min.
[0088] S3. Reduce the rotation speed to 400 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1500 rpm. After dispersing for 12 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0089] S4. Transfer the material back to the dispersion tank and disperse it at 400 rpm for 4 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1500 rpm and continue to disperse for 22 minutes.
[0090] S5. Reduce the rotation speed to 400 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1500 rpm for 15 minutes, filter and dispense to obtain ingredient A.
[0091] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse at 800 rpm for 8 min, filter and dispense to obtain ingredient B.
[0092] S7. By weight, mix 100 parts of ingredient A with 3 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0093] Example 5: Prepare the raw materials according to the formula and dosage shown in Table 4 below.
[0094] Table 5: Raw Material Formula Table
[0095] Mix component A to form ingredient A, mix component B to form ingredient B, and then prepare the coating by following these steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 60% of the solvent by mass, and stir and disperse at 600 rpm for 5 min.
[0096] S2. Reduce the rotation speed to 300 rpm, slowly add the TPE-PDMS-OH polymer, and after the addition is complete, increase the rotation speed to 1500 rpm and disperse for 15 min.
[0097] S3. Reduce the rotation speed to 300 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1000 rpm. After dispersing for 15 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0098] S4. Transfer the material back to the dispersion tank and disperse it at 300 rpm for 5 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1000 rpm and continue to disperse for 20 minutes.
[0099] S5. Reduce the rotation speed to 300 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1000 rpm for 15 minutes, filter and dispense to obtain ingredient A.
[0100] S6. Add the polyisocyanate curing agent to the dispersion tank, disperse at 800 rpm for 5 min, filter and dispense to obtain ingredient B.
[0101] S7. By weight, mix 100 parts of ingredient A with 3 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0102] Comparative Example 1: Comparative Example 1 prepared a coating using the same raw materials and methods as in Example 4, except that the TPE-PDMS-OH polymer was not used. The other raw materials and their amounts were the same as in Example 4.
[0103] The preparation method omits the step for adding the TPE-PDMS-OH polymer (i.e., remove the original step S2), specifically: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to the dispersion tank, add 80% of the solvent by mass, and stir and disperse at 900 rpm for 3 min.
[0104] S2. Reduce the rotation speed to 400 rpm, slowly add the metal powder and superconducting carbon black, and after the addition is complete, increase the rotation speed to 1500 rpm. After dispersing for 12 minutes, transfer to a sand mill for grinding until the fineness is less than 80 μm.
[0105] S3. Transfer the material back to the dispersion tank and disperse it at 400 rpm for 4 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1500 rpm and continue to disperse for 22 minutes.
[0106] S4. Reduce the rotation speed to 400 rpm, add the adhesion promoter, defoamer and remaining solvent, stir at 1500 rpm for 15 minutes, filter and dispense to obtain ingredient A.
[0107] S5. Add the polyisocyanate curing agent to the dispersion tank, disperse at 800 rpm for 8 min, filter and dispense to obtain ingredient B.
[0108] S6. By weight, mix 100 parts of ingredient A with 3 parts of ingredient B, stir evenly to obtain an anti-icing conductive coating for contact wires.
[0109] Comparative Example 2: Comparative Example 2 prepared a coating according to the raw materials and methods of Example 4, except that the TPE-PDMS-OH polymer was not used and the amount of superconducting carbon black was changed from 3 parts to 1 part; the other raw materials used and their amounts were the same as in Example 4.
[0110] The preparation method is the same as that provided in Comparative Example 1.
[0111] Test Example 1: The coatings obtained in Examples 1-5 and Comparative Examples 1-2 were uniformly applied to identical substrates meeting the same testing standards using air spraying, forming a coating of 50-80 μm / thickness. The resulting coatings were tested using the following testing standards or methods: GB / T 45017-2004 Test method for mechanical stability of hydrophobic surfaces; GB / T 3048.2-2007 Electrical performance test methods for wires and cables - Part 2: Resistivity test for metallic conductor materials; HG / T 5367.5-2022 Coatings for Rail Transit Vehicles - Part 5: Anti-icing Coatings; GB / T 1768 Determination of abrasion resistance of paints and varnishes by rotating rubber grinding wheel method; GB / T 1731-1993 "Determination of Flexibility of Paint Films"; GB / T 5210 Paints and varnishes—Pull-off adhesion test; GB / T 528 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.
[0112] The test indicators include photothermal properties, hydrophobicity and oleophobicity, initial icing force and icing force after aging, electrical conductivity, abrasion resistance, de-icing rate, flexibility, adhesion, etc. The test results are shown in Table 6 below.
[0113] Table 6 Summary of test results for coatings prepared in Examples 1-5 and Comparative Examples 1-2
[0114] The test results in Table 6 are analyzed below: Regarding hydrophobicity, the coatings made from the paint provided in this application exhibit a water contact angle of up to 175°, and in all the test results provided by the embodiments, the water contact angle is ≥165°, proving that the coatings provided in this application have a superhydrophobic effect. Simultaneously, the roll-off angle is less than 2.5°, further demonstrating that the coatings provided in this application, in addition to excellent hydrophobicity, also possess excellent self-cleaning properties. Surface dirt can be removed with rinsing, which is highly valuable in practical applications. Regarding oleophobicity, the coatings provided in all embodiments achieved an oil (n-hexadecane) contact angle ≥122°, proving that the coatings provided in this application have excellent oleophobic effects.
[0115] As can be seen from the table, the coatings provided in Examples 1-5 exhibit excellent anti-icing effects: the horizontal icing force is below 15N, with the optimal value (Example 5) being only 10N; and the de-icing rate is 95%-98%. This demonstrates that even if ice and snow accumulate on the contact wire after coating with the coatings provided in this application, they will be removed due to wind, snow melting, and contact wire vibration, effectively preventing prolonged accumulation and coverage of ice and snow on the contact wire in practical use. Furthermore, the data in the table shows that the change in icing force after coating aging (i.e., the increase in horizontal icing force after coating aging) is small, proving that the coating maintains excellent anti-icing effects even after long-term use and natural aging. In addition, the test results of the coatings provided in Comparative Examples 1-2 are inferior to those provided in Examples 1-5 in terms of icing force, change in icing force after aging, and de-icing rate, showing a consistent pattern. The applicant believes the reason may be that: Comparative Example 1 used the most carbon black in the range without simultaneously using TPE-PDMS-OH polymer, which made the coating system have high oil absorption, thus affecting the reasonable ratio of the base resin and other materials. The coating was not flexible and dense enough, and ice and snow were more likely to cover and accumulate. This was reflected in the test results as a large ice-holding power value and a poor de-icing rate.
[0116] Furthermore, the coatings provided in Examples 1-5, when used to form coatings, exhibit a temperature increase of 25-30°C per minute under 1 solar radiation intensity, demonstrating the excellent photothermal properties of the coatings provided in this application. Moreover, the electrical conductivity is consistently below 6.1 × 10⁻⁶. 7 It has a conductivity of over µS / m and exhibits excellent electrical conductivity.
[0117] In terms of mechanical properties, the abrasion resistance test results were low, below 12; that is, under a test load of 1000 grams and 1000 rotations, the amount of wear was less than 12 mg, proving that the coating provided in this application has excellent abrasion resistance. The adhesion was all above 15 MPa, indicating strong adhesion to the substrate. Furthermore, the flexibility reached 1 mm, proving that the coating provided in this application has excellent toughness and elasticity, good resistance to deformation, and can meet the requirement of not cracking or breaking under vibration. Moreover, comparing the data from the examples and comparative examples (Example 4 had the best abrasion resistance and adhesion values, while the values of Comparative Examples 1 and 2 were worse than any of the data from Examples 1-5, showing a regularity), it is proven that the TPE-PDMS-OH polymer has a significant enhancing effect on the abrasion resistance, toughness, and adhesion of the coating.
[0118] As can be seen from the above, the coating provided in this application has been tested on a slab and has excellent hydrophobic and oleophobic properties, anti-icing properties, photothermal properties, electrical conductivity, and mechanical properties. It can effectively reduce the amount of ice forming on the surface of the contact network and achieve natural de-icing at low temperatures. At the same time, it has excellent wear resistance and toughness, and strong adhesion, which can meet the operating friction and conductivity requirements between the contact network and the pantograph, and can solve the operating needs of the contact network in low-temperature and harsh weather conditions.
[0119] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A conductive coating for contact wires that prevents icing, comprising component A and component B, characterized in that, By weight, component A comprises 12–25 parts modified fluorosilicone resin, 0.6–1.2 parts fluorinated modified nano-SiO2, 2–4 parts TiN / graphene composite material, 2–4 parts graphene / carbon fiber composite material, 2–4 parts tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer, 1–2 parts metal powder, 1–3 parts superconducting carbon black, 0.1–0.5 parts adhesion promoter, 0.2–0.6 parts wetting and dispersing agent, 0.1–0.3 parts defoamer, and 60–80 parts solvent; component B comprises 1.5–4 parts polyisocyanate curing agent. The tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer comprises molecules with the structure shown in formula (1): , structure (1); where n = 15 ~ 50.
2. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The preparation method of the TiN / graphene composite material includes the following steps: S1. By mass, add 30 parts of TiN powder to 70 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain TiN dispersion; S2. Add 10 parts of graphene to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain a graphene dispersion; S3. Mix the TiN dispersion and graphene dispersion at a mass ratio of 1:1, heat and disperse for 1 hour, and then dry.
3. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The preparation method of the graphene / carbon fiber composite material includes the following steps: S1. By mass, add 10 parts of graphene powder to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and disperse evenly to obtain a graphene dispersion. S2. Add 10 parts of carbon fiber to 90 parts of solvent, add 1 part of polyvinylpyrrolidone, and ultrasonically disperse to obtain a carbon fiber dispersion; S3. Mix the graphene dispersion and carbon fiber dispersion at a mass ratio of 1:1, disperse by ball milling, and then dry.
4. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The preparation method of the tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer includes the following steps: S1. Place 4-carboxytetraphenylethylene, hydroxyl-terminated silicone oil and anhydrous dichloromethane in a reactor and stir until dissolved under a nitrogen atmosphere; S2. After adding 4-dimethylaminopyridine, cool to 0-5°C and add N,N'-dicyclohexylcarbodiimide while stirring; after the addition is complete, return to room temperature. S3. Stir the reaction continuously at room temperature for 24–36 hours; S4. The reactants are filtered, concentrated, purified, washed, dried and purified.
5. The anti-icing conductive coating for contact wires according to claim 4, characterized in that, The preparation method of 4-carboxytetraphenylethylene in step S1 includes the following steps: S11. Under a nitrogen atmosphere, 4-formyltetraphenylethylene is placed in a reactor, anhydrous acetone is added and stirred until dissolved; S12. Cool to 0-5℃, and slowly add Jones' reagent dropwise while stirring; after the addition is complete, raise to room temperature and stir the reaction for 1-2 hours. S13. Add isopropanol solution and stir, then extract using an extractant, which can be either dichloromethane or ethyl acetate; S14. Wash with deionized water and saturated sodium chloride solution, then dry with anhydrous sodium sulfate, filter and collect the filtrate, and concentrate by rotary evaporation to obtain the finished product.
6. The anti-icing conductive coating for contact wires according to claim 4, characterized in that, Step S4 specifically includes: Filter the reactants to remove solid impurities and collect the filtrate. Then concentrate the filtrate to one-third of its volume, add 3 to 5 times its volume of diethyl ether and place it in an environment below 0°C for cold precipitation to remove impurities. Filter to remove solid impurities and obtain an organic phase filtrate. Wash the filtrate successively with dilute hydrochloric acid solution, saturated sodium bicarbonate solution and saturated sodium chloride solution, then dry it with anhydrous sodium sulfate, filter to collect the filtrate and concentrate it by rotary evaporation to remove the solvent.
7. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The metal powder is in flake form and its components include at least one of silver powder and copper powder.
8. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The specific surface area of the superconducting carbon black powder is 400-500 m². 2 / g.
9. The anti-icing conductive coating for contact wires according to claim 1, characterized in that, The wetting and dispersing agent is polyvinylpyrrolidone.
10. The method for preparing the anti-icing conductive coating for contact wires according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. Add the modified fluorosilicone resin and wetting and dispersing agent to a dispersion tank, add some solvent, and stir and disperse at 600-900 rpm for 3-5 min; S2. Reduce the rotation speed to 300-400 rpm, slowly add the tetraphenylethylene-grafted hydroxyl-terminated polydimethylsiloxane polymer, and after the addition is complete, increase the rotation speed to 1000-1200 rpm and stir to disperse for 15-30 minutes. S3. Reduce the rotation speed to 300-400 rpm, slowly add metal powder and superconducting carbon black, and after adding, increase the rotation speed to 1000-1500 rpm, stir and disperse for 10-15 minutes, and then transfer to a sand mill for grinding until the fineness is less than 80 μm. S4. Transfer the material back to the dispersion tank and stir and disperse at 300-500 rpm for 3-5 minutes. Add fluorinated modified nano-SiO2, TiN / graphene composite material, and graphene / carbon fiber composite material in sequence. After the addition is complete, increase the speed to 1000-1500 rpm and stir and disperse for 20-25 minutes. S5. Reduce the rotation speed to 300-500 rpm, add adhesion promoter, defoamer and remaining solvent, and stir at 1000-1500 rpm for more than 10 minutes to obtain ingredient A for later use. S6. Add the polyisocyanate curing agent to the dispersion tank and disperse it at 600-900 rpm for 5-8 min to obtain ingredient B for later use; S7. By weight, mix 100 parts of ingredient A with 1.5 to 4 parts of ingredient B and stir until homogeneous.